(untitled) (Advances in Applied Biological Research, 2026)
The study investigated the impact of effluents from chemical and textile industries on the physicochemical characteristics of the Chambal River over a one-year period. Water samples were collected quarterly across three seasons from five designated stations along the river, selected based on proximity to major industrial discharge points. Stations 2, 3, and 4, which received direct effluent inputs, exhibited slight increases in pH, BOD, and COD values. Statistical analysis using the t-test revealed significant differences in turbidity, TDS, TSS, electrical conductivity, DO, chloride, sulphate, and hardness among the sampling stations. In contrast, the upstream (Station 1) and downstream (Station 5) reference sites recorded comparatively lower values for these parameters. Seasonal variation had minimal influence on most parameters, except for chloride, sulphate, and TDS, which showed significant differences across sampling periods. The findings highlight the urgent need for remediation programs to mitigate the deteriorating water quality in affected sections of the river.